Systematic Development of Correct Bulk Synchronous Parallel Programs - Gesbert, L; Zhenjiang Hu; Loulergue, Frédéric; Matsuzaki, K; Tesson, J (2010 International Conference on Parallel and Distributed Computing, Applications and Technologies, 2010)
With the current generalisation of parallel architectures arises the concern of applying formal methods to parallelism. The complexity of parallel, compared to sequential, programs makes them more error-prone and difficult to verify. Bulk Synchronous Parallelism (BSP) is a model of computation which offers a high degree of abstraction like PRAM models but yet a realistic cost model based on a structured parallelism. We propose a framework for refining a sequential specification toward a functional BSP program, the whole process being done with the help of the Coq proof assistant. To do so we define BH, a new homomorphic skeleton, which captures the essence of BSP computation in an algorithmic level, and also serves as a bridge in mapping from high level specification to low level BSP parallel programs.